Obsessive compulsive disorder due to ingestion of single dose ecstasy: a case report - Semiz, Ü. B.; Algül, A.; Güneş, C.; Ateş, A.; Başoğlu, C.; Ebrinç, S.; Çetin, M. (Journal of Dependence, 2008)
Ecstasy (3, 4-methylenedioxymethamphetamine, MDMA) is a widely abused substance. Many different persistent psychiatric disorders thought to be caused by ecstasy have been reported in the literature. There is increasing evidence that ecstasy causes permanent damage to serotonergic neurons. This article presents a case of obsessive-compulsive disorder (OCD) that developed after a single ecstasy use. The patient reported experiencing fatigue and remorse after ecstasy use. He subsequently became unable to touch anything due to fear of accidentally ingesting ecstasy dust. He felt a constant need to wash his hands. He had been experiencing religious obsessions for the past year. He had never seen a psychiatrist before and had never received treatment. This article reviews the possible mechanisms of action and neuronal effects of ecstasy.
Keywords: ecstasy use